Análisis de la Planta Turística oferta de alojamiento en La Maná - Jaramillo Herrera, Silvia Elizabeth (2019)
With the present research work, a catalog of the tourist accommodation facilities of La Maná canton was designed, this tool serves to inform to the inhabitants, tourists and visitors. Through methods, techniques and research instruments used to collect, interpret and analyze the information obtained through the field study, and with this inventory the accommodation establishments. After the description and analysis of the diagnosis and inventory information, it was determined that La Maná canton has a lot of tourist potential, but it is necessary to improve the infrastructure, focusing on the necessary conditions for the comfort that the tourist requires. Eleven hotels, a hostel and three inns were inventoried, of which fourteen establishments belong to the category of two stars and a hotel to the category of four stars; and according to the complementary services in the accommodation area, most of the establishments do not offer half of the services described in the technical file created by the Ecotourism Career and neither they have complied with the accommodation rules required by the tourism regulations. With the lodging catalog, we present all the options of establishments dedicated to this purpose and with a variety of services for all tourist profiles. With the research work we want to motivate to the owners of the establishments to offer an excellent customer service by improving the accommodation infrastructure to increase the visits of tourists in the area, since this is a very important factor because it affects to the tourist development of the canton. In addition, this project will serve for future research and it is important that the information is updated periodically because there are many establishments that have projects to improve their services.